1994
DOI: 10.1002/ppul.1950180204
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the ability of young children to use a powder inhaler device (Turbuhaler)

Abstract: The purpose of the study was to determine the age at which young asthmatic children could master the use of a new powder inhaler device (Turbuhaler). We studied 59 children with asthma between the ages of 3 and 6 years who consecutively attended the asthma clinic of the pediatric department. Efficiency of inhalation and the pharmacological effect of the terbutaline in the inhaler were measured by scores for inhalation technique and clinical response. None of the 3-year-old children used the device efficiently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 9 publications
3
30
0
1
Order By: Relevance
“…Incorrect or inefficient inhaler usage may be a direct consequence of poor instruction, 39 but this is improved (albeit temporarily) by training. 40,41 The quality of this training is of paramount importance. The manufacturer's instruction sheet alone is ineffective in achieving correct technique.…”
Section: Resultsmentioning
confidence: 99%
“…Incorrect or inefficient inhaler usage may be a direct consequence of poor instruction, 39 but this is improved (albeit temporarily) by training. 40,41 The quality of this training is of paramount importance. The manufacturer's instruction sheet alone is ineffective in achieving correct technique.…”
Section: Resultsmentioning
confidence: 99%
“…The strongest confirmation of the value of inhaler checklists comes from studies in which inhaler assessment and skills training were associated with significantly improved asthma outcomes. 14 Again, there are few studies, but in young children, Goren et al 73 showed that improved Turbuhaler technique with a rudimentary child-specific checklist was associated with greater bronchodilator effect. In the 6-month study by Basheti et al, 14 a brief pharmacy intervention, with assessment and correction of inhaler technique and checklistbased inhaler labels, led to significant improvement in asthma outcomes compared with a control group.…”
Section: Clinical Impact Of Using Inhaler Technique Checklistsmentioning
confidence: 99%
“…Studies in children have indicated that, above the age of 5 yrs, most children can generate PIFs above 30 L·min -1 when inhaling through the Turbuhaler®, but that below this age PIFs above 30 L·min -1 are less common [14]. Despite this, clinical studies have indicated that useful clinical effects can be demonstrated in preschool children as young as 3 yrs of age [19,20].…”
mentioning
confidence: 97%